Application of artificial intelligence in the prevention of fraud in financial statements - Septiriana, Rina; Widianto, Septian Rheno; Darma, Putri Ekawati (Jurnal Ekonomi, 2024)
This study examines the use of artificial intelligence (AI) through the ACL Analytic programme to avoid fraud on financial accounts. The findings demonstrate that the ACL Analytic programme is proficient in detecting possibly deceptive transactions, enhancing temporal efficiency in the audit procedure, and aiding in scrutinising substantial amounts of data with superior swiftness and precision compared to conventional approaches. Traditional techniques for preventing fraud are often inadequate against the evolving strategies employed by fraudsters, necessitating a more advanced and adaptable strategy. Due to the exponential increase in data volume, firms have challenges in conducting comprehensive analysis of financial information. Artificial intelligence (AI) presents a potential solution to this problem by offering the capability to process and analyse data on a significantly greater magnitude. The research employed a case study approach, enabling the researcher to thoroughly examine the implementation of artificial intelligence using the ACL Analytic application within the realm of preventing financial statement fraud. The study's findings offer a thorough comprehension of the efficacy of utilising artificial intelligence via ACL Analytic for the purpose of preventing financial statement fraud. Additionally, it offers valuable insights for other companies and financial institutions considering the adoption of similar technology.